A novel method enabling the accurate quantification of microplastics in the water column of deep ocean. (September 2019) - Liu, Kai; Zhang, Feng; Song, Zhangyu; Zong, Changxing; Wei, Nian; Li, Daoji
Abstract: Little information concerning microplastic (MP) pollution in the deep ocean is currently available, and a huge gap exists between sampling methodology and obtaining an authentic dataset. Verified sampling methodology is a fundamental step in the accurate determination of MP pollution in the pelagic environment, of which sample volume is a crucial factor. To address this methodological challenge, in situ filtration technology, a novel sampling method for microplastics in the water column, was proposed and investigated. On 27 April 2019, we took the East China Sea as a typical example in order to determine the relationship between sample volume and MP abundance. Analysis indicated that the filtrated volume has an impact on MP quantification and significant exponential regression between the sample volume and MPs was observed. This investigation indicated that a small volume sample could easily lead to MP overestimation, with at least 8 m 3 water required to obtain reliable data. Highlights: The sampling methodology for deep sea MP pollution was introduced and discussed. A novel sampling method for MP quantification in the water column was proposed. The relationship between sample volume and MP abundance was explored. The proper volume of filtrated water was investigated and recommended.